2007
DOI: 10.1080/02841850701557255
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography features of recurrent ovarian carcinoma according to time to relapse

Abstract: Our study is the first to describe common patterns of recurrence in ovarian cancer. Most frequent site is pelvis, followed by peritoneum, serosal surfaces and nodal disease. 30% presented with disease at 'unusual' sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We demonstrated in the present study that ovarian cancers recur most commonly as peritoneal metastases and lymph node metastasis, supporting the evidence that common sites of ovarian cancer recurrence include the pelvic mass, peritoneal metastases and enlarged lymph nodes (14,15), the pleura, and the lung (15). Furthermore, we specified the common anatomical location of peritoneal metastases as solid nodules rather than cystic lesions.…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated in the present study that ovarian cancers recur most commonly as peritoneal metastases and lymph node metastasis, supporting the evidence that common sites of ovarian cancer recurrence include the pelvic mass, peritoneal metastases and enlarged lymph nodes (14,15), the pleura, and the lung (15). Furthermore, we specified the common anatomical location of peritoneal metastases as solid nodules rather than cystic lesions.…”
Section: Discussionsupporting
confidence: 89%
“…In our patient, the time to recurrence, 23 years after the diagnosis, was unusually long. A retrospective study including 400 patients with ovarian cancer showed that 87% of relapses occurred within 5 years following primary treatment, 8% relapsed between 5-10 years and 6% relapsed after 10 years (5). Very late relapses, after more than 20 years have only rarely been reported for invasive ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that, although EOC typically colonized a wide variety of organs and tissues, there was not one single metastatic site that was always involved by metastasis in all studied cases. The main site of metastasis was the peritoneum, including the parietal and visceral peritoneum and omentum, which was involved in 77% of cases on average among several reports (ranging between 53% and 99%, Table 1 ) [ 25 , 26 , 27 , 29 , 30 , 31 ]. Other commonly colonized sites identified by autopsy studies included lymph nodes (38–77% of cases), large and small intestine (44–86% of cases), liver parenchyma (45–59% of cases), and lung (33–39% of cases).…”
Section: Sites Of Eoc Metastasesmentioning
confidence: 99%